Changes in self-regulated learning profiles during an undergraduate peer-based intervention: A latent profile transition analysis. (February 2023) - Jeong, Soojeong; Feldon, David F.
Abstract: University students often have insufficient strategies to regulate their own learning independently, suggesting the need for adequate support. This study examined developmental changes in students' self-regulated learning (SRL) profiles during their participation in Supplemental Instruction, a peer-based intervention, over the course of a semester and predictive variables of these changes. Latent profile transition analysis of a sample of 352 undergraduates revealed three distinct SRL profiles which emerged identically across time points: competent regulators, self-confident regulators, and goal-oriented regulators . Students in the competent regulators profile were most stable over time, while those in the goal-oriented regulators profile were most malleable, but in a positive sense. Results also indicate that students who attributed SI attendance to mastery goals were more likely to transition beneficially between SRL profiles. The observed predictors of transitions between profiles also highlighted the relative importance of motivational variables as opposed to cognitive-metacognitive variables in accounting for SRL development. Highlights: Results revealed three SRL profiles in undergraduate students participating in SI. Students in the competent regulators profile were most stable during SI. Students in the goal-oriented regulators profile were most malleable during SI. Students who attributed SI attendance to mastery goals transitioned beneficially. Motivational variables were stronger predictors of SRL development.